A Microfluidic System for Simultaneous Raman Spectroscopy, Patch‐Clamp Electrophysiology, and Live‐Cell Imaging to Study Key Cellular Events of Single Living Cells in Response to Acute Hypoxia. Issue 10 (21st August 2021) - Knoepp, Fenja; Wahl, Joel; Andersson, Anders; Kraut, Simone; Sommer, Natascha; Weissmann, Norbert; Ramser, Kerstin
Abstract: The ability to sense changes in oxygen availability is fundamentally important for the survival of all aerobic organisms. However, cellular oxygen sensing mechanisms and pathologies remain incompletely understood and studies of acute oxygen sensing, in particular, have produced inconsistent results. Current methods cannot simultaneously measure the key cellular events in acute hypoxia (i.e., changes in redox state, electrophysiological properties, and mechanical responses) at controlled partial pressures of oxygen (pO2 ). The lack of such a comprehensive method essentially contributes to the discrepancies in the field. A sealed microfluidic system that combines i) Raman spectroscopy, ii) patch‐clamp electrophysiology, and iii) live‐cell imaging under precisely controlled pO2 have therefore been developed. Merging these modalities allows label‐free and simultaneous observation of oxygen‐dependent alterations in multiple cellular redox couples, membrane potential, and cellular contraction. This technique is adaptable to any cell type and allows in‐depth insight into acute oxygen sensing processes underlying various physiologic and pathologic conditions. Abstract : This work describes a microfluidic system, developed to meet the demand for simultaneous and label‐free assessment of the key cellular features underlying all mammalian oxygen‐sensing processes. The device is transferrable to any cell type and provides the unique opportunity to measure directly and simultaneously the cellular/mitochondrial redox state, electrophysiological properties, and contractility of single living cells under tight oxygen‐control.